2012
DOI: 10.1016/j.peptides.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal properties of Canavalia ensiformis urease and derived peptides

Abstract: Ureases (EC 3.5.1.5) are metalloenzymes that hydrolyze urea into ammonia and CO(2). These proteins have insecticidal and fungicidal effects not related to their enzymatic activity. The insecticidal activity of urease is mostly dependent on the release of internal peptides after hydrolysis by insect digestive cathepsins. Jaburetox is a recombinant version of one of these peptides, expressed in Escherichia coli. The antifungal activity of ureases in filamentous fungi occurs at submicromolar doses, with damage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 42 publications
2
46
0
1
Order By: Relevance
“…Indeed, the presence of this tag does not interfere with the biological insecticidal [17] and fungicidal [20] activities of this urease-derived peptide. The expression protocol of Jaburetox was optimized in this work to typically yield 30 mg of Jaburetox per liter of culture.…”
Section: Jaburetox Expression and Purificationmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, the presence of this tag does not interfere with the biological insecticidal [17] and fungicidal [20] activities of this urease-derived peptide. The expression protocol of Jaburetox was optimized in this work to typically yield 30 mg of Jaburetox per liter of culture.…”
Section: Jaburetox Expression and Purificationmentioning
confidence: 97%
“…parapsilosis, Ca. tropicalis, Kluyveromyces marxianus, Pichia membranisfaciens and Saccharomyces cerevisiae), in addition to its entomotoxic activity [20]. In order to understand the mode of action of Jaburetox-2Ec, molecular modeling studies were carried out that suggested the existence of a b-hairpin motif at the C-terminal portion [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Es probable que la integridad y funcionalidad de los hongos ruminales se afectada por los FAN de canavalia, debido a que C. ensiformis produce isoformas de ureasa con acción insecticida y fungicida (Becker-Ritt et al 2007). La ureasa más abundante es JBURE-I, seguida por la canatoxina y JBURE-IIB, la toxicidad de la ureasa de canavalia ocurre en dosis micromolares y varía con el género y especie de hongo, causando inhibición de la proliferación, alteraciones morfológicas en la pared y membrana, cambios en el transporte de H + y en la permeabilidad de la membrana, lo que induce a la muerte celular (Postal et al 2012).…”
Section: Biana Del Rumenunclassified
“…The data obtained by Martinelli et al [14] brought important contributions to the understanding of the JBTX’s mechanism of action, suggesting that it represents a new type of active peptide in membranes, with insecticidal and fungitoxic properties. The antifungal activity of JBTX against yeasts occurs at higher doses (9 to18 μM) than those observed for JBU (0.27 μM), suggesting that other regions of the protein could probably be involved in this activity [11]. …”
Section: Introductionmentioning
confidence: 99%